1277. Provider Perspectives on Long-Acting Injectable Antiretroviral Therapy: A "Golden Ticket"?. (15th December 2022) - Uhrig Castonguay, Breana J; Carda-Auten, Jessica; Rodriguez, Humberto Gonzalez; Mayer, Kenneth H; Wohl, David A; Kerrigan, Deanna; Barrington, Clare; Fernandez, Ricardo F
Abstract: Background: Long-acting injectable antiretroviral therapy (LAI-ART) has been approved as an alternative to daily oral ART for people living with HIV (PLWH). Amidst the promise and potential challenges of LAI-ART, acceptability of this new therapeutic option remains largely unexplored beyond clinical trials. The aim of this study is to characterize perceptions and preferences related to LAI-ART among HIV care providers (HCPs). Methods: We conducted qualitative in-depth interviews with 32 HCPs from three distinct geographic areas (Boston, MA; Chapel Hill, NC; Washington, DC) between November 2019 to March 2021. HCPs included: physicians, nurse practitioners, physician assistants, registered nurses, clinical pharmacists, social workers, medical assistants, and HIV navigators. We developed narrative summaries to understand individual perspectives and then systematically coded transcripts using Dedoose to identify recurring themes across participants. Results: HCPs felt LAI-ART could be the "golden ticket" for patients who struggle with adherence or worry about HIV status disclosure. However, they perceived patient interest in LAI-ART would vary based on several factors. HCPs expected older patients who have lived with HIV longer and are reluctant to changing regimens, those who live far from clinic, or have a fear of needles to be less interested in LAI-ART. A recurring concern among HCPs was that LAI-ART will require frequent clinic visits, making it more burdensome to both patients and clinics. HCPs overwhelmingly preferred an 8-week over a 4-week dose schedule. To support introduction of LAI-ART, HCPs wanted: 1) clinic-wide trainings; 2) recommendations for optimal viral suppression status at LAI-ART initiation; 3) protocols for managing missed/late doses; and 4) implementation guidance to manage staff time tracking patients on LAI-ART. Conclusion: Findings highlight the importance of understanding HCP perceptions, expectations, and concerns as these are likely to influence treatment discussions with PLWH and integration of LAI-ART. HCPs' concerns and uncertainty regarding implementation, highlight the need for provider resources to support decision-making around LAI-ART. Additionally, clinic level guidance for the logistics of roll-out are urgently needed. Disclosures: Kenneth H. Mayer, MD, Gilead: Advisor/Consultant|Merck: Advisor/Consultant|ViiV: Advisor/Consultant David A. Wohl, M.D., Gilead: Advisor/Consultant|Gilead: Grant/Research Support|Janssen: Advisor/Consultant|Lilly: Grant/Research Support|Merck: Grant/Research Support|ViiV: Advisor/Consultant|ViiV: Grant/Research Support.